2022
DOI: 10.1021/acsbiomaterials.2c00873
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Processing of Dynamic Covalently Crosslinked Polydextran/Carbon Dot Nanocomposite Hydrogels with Tailorable Microstructures and Properties

Abstract: Using functionalized nanoparticles to crosslink hydrophilic polymers is a growing theme of directly constructing nanocomposite (NC) hydrogels. Employing dynamic covalent chemistry at the nanoparticle–polymer interface is particularly attractive due to the spontaneous formation and reversible manner of dynamic covalent bonds. However, the structure and property modulation of the dynamic covalently crosslinked NC hydrogels has not been thoroughly discussed. Here, we fabricated NC hydrogels by using amine-functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…They also demonstrated that the chemically crosslinked SN hydrogel had pores of varying sizes (50–100 µm) and a porous structure. NC hydrogels were developed by Lu et al by crosslinking polydextran aldehyde (PDA) polymers by imine bond synthesis utilizing amine-functionalized carbon dots (CDs) [ 107 ]. It was found that among the three PDA@CD hydrogels ( Figure 10 ) tested, the PDA50@CD hydrogel had the densest structure and maximum mechanical strength due to its higher oxidation degree compared to the other two hydrogels.…”
Section: Fabrication Techniques Of Carbon Dots Reinforced Hydrogelsmentioning
confidence: 99%
“…They also demonstrated that the chemically crosslinked SN hydrogel had pores of varying sizes (50–100 µm) and a porous structure. NC hydrogels were developed by Lu et al by crosslinking polydextran aldehyde (PDA) polymers by imine bond synthesis utilizing amine-functionalized carbon dots (CDs) [ 107 ]. It was found that among the three PDA@CD hydrogels ( Figure 10 ) tested, the PDA50@CD hydrogel had the densest structure and maximum mechanical strength due to its higher oxidation degree compared to the other two hydrogels.…”
Section: Fabrication Techniques Of Carbon Dots Reinforced Hydrogelsmentioning
confidence: 99%